Saneamento rural e saúde das crianças em Jaboticatubas - Minas Gerais, 2001 - Romero Alves Teixeira (2003)
To describe the housing conditions, socioeconomic, cultural, demographic and health which are associated with infant diarrhea in the rural area of Jaboticatubas, we studied a random sample of 463 children younger than 10 years. It was found in a household survey, information on the prevalence of diarrhea, and environmental sanitation variables, demographic characteristics, education and employment of parents, family income, breastfeeding and infant morbidity. We performed a univariate analysis, we calculated odds ratios and confidence intervals. Associations were found between diarrhea and, excreta disposal, presence of cockroaches, overcrowding in housing, poor hygiene and cleanliness of the floor, child age, maternal age and education, family income, unemployment of the household head, illness, and previous admissions to interview. The results showed that the environmental, cultural and socioeconomic conditions are important risk factors for childhood diarrhea, suggesting the need to expand coverage of cesspools, a program for protection and income generation, and expanding the coverage of health program Family, focusing on childhood diarrhea, acute respiratory diseases, increased rates of breastfeeding and health education.